2017
DOI: 10.4081/pmc.2017.183
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional problems of children with bronchopulmonary dysplasia after hospital discharge

Abstract: The last decades have seen significant improvements in the care of premature infants. The introduction of new approaches, especially in the ventilatory management, have led to significant increase of survival rate of low and extremely low gestational age infants. These populations of neonates, however, often experience prolonged mechanical ventilation, which is widely recognized to be closely related to bronchopulmonary dysplasia (BPD) development.The management of BPD, which is a multifactorial disease, requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Prematurity affects multiple systems with potentially lifelong consequences [ 68 ], Crump et al have suggested that “preterm birth should be recognized as a chronic condition that requires long-term follow-up” [ 69 ]. The European Foundation for the Care of Newborn Infants (EFCNI) has developed standards of care for infants born preterm from birth to school age.…”
Section: Other Areas Of Interventionmentioning
confidence: 99%
“…Prematurity affects multiple systems with potentially lifelong consequences [ 68 ], Crump et al have suggested that “preterm birth should be recognized as a chronic condition that requires long-term follow-up” [ 69 ]. The European Foundation for the Care of Newborn Infants (EFCNI) has developed standards of care for infants born preterm from birth to school age.…”
Section: Other Areas Of Interventionmentioning
confidence: 99%
“…Optimal growth is essential for the infant with BPD to be successfully weaned from oxygen and to continue the delayed alveolarization that can occur during childhood. One of the criteria for weaning oxygen is adequate growth and weight gain (goal of 20–30 g/d) 59 . Although breastfeeding is encouraged, many of these infants will require additional fortified breastmilk or formula to maintain adequate caloric intake and mineral supplementation.…”
Section: Approach To Nutritional Management Of Infants and Children With Bpdmentioning
confidence: 99%